Long-term exposure to air pollution and risk of Sarcopenia in adult residents of Taiwan: a nationwide retrospective cohort study - Ssu-Wen Chen; Chih-Ying Lin; Chiu-Ying Chen; Cheng-Li Lin; Tsai-Ling Hsieh; Fuu-Jen Tsai; Kuang-Hsi Chang (BMC, 2023)
Abstract Background Sarcopenia is an age-related, multifactorial syndrome. Previous studies have shown that air pollutants are associated with inflammation and oxidative stress. However, the association between long-term exposure to air pollution and sarcopenia is not completely understood. Methods The Taiwan National Health Research Database (NHIRD) contains medical records of almost all Taiwanese residents. Daily air pollution data collected by the Taiwan Environmental Protection Agency was used to analyze concentrations of sulfur oxide (SO2), carbon monoxide (CO), nitrogen monoxide (NO), nitrogen dioxide (NO2), and particulate matter (PM2.5, PM10). The databases were merged according to the insurants' living area and the location of the air quality monitoring station. We categorized the pollutants into quartiles (Q1, Q2, Q3, and Q4). Results Our study population consisted of 286,044 patients, among whom 54.9% were female and 45.1% were male. Compared to Q1 levels of pollutants, Q4 levels of SO2 (adjusted hazard ratio [aHR] = 8.43; 95% confidence interval [CI] = 7.84, 9.07); CO (aHR = 3.03; 95%CI = 2.83, 3.25); NO (aHR = 3.47; 95%CI = 3.23, 3.73); NO2 (aHR = 3.72; 95%CI = 3.48, 3.98); PM2.5 (aHR = 21.9; 95% CI = 19.7, 24.5) and PM10 (aHR = 15.6; 95%CI = 14.1, 17.4) increased risk of sarcopenia. Conclusions Our findings indicated a significantly increased risk of sarcopenia in both male and female residents exposed to high levels of air pollutants.